Dendrimers as potential platform in nanotechnology-based drug delivery systems - Silva Júnior, Nelson; Menacho, F. P.; Chorilli, Marlus [UNESP] (My University, 2012)
The dendrimers of poly (amidoamine) (PAMAM) are nanoparticles which have proven succeed in transporting drugs due to high solubility, low toxicity and ability to control drugs release. Studies have explored the biological potential of dendrimers such as to transport genes, development of vaccines, antiviral, antibacterial and anticancer therapies. This review of literature on the PAMAM dendrimers discusses the architecture and general construction of dendrimers and intrinsic properties of the PAMAM. This study also describes how the PAMAM interact with many drugs and the potential of these macromolecules as well as drug nanocarriers in transdermal routes of administration, ocular, respiratory, oral and intravenous administration. Dendrimers promises good future prospects for the biomedicine.
Keywords: Dendrimers; Nanocarriers; PAMAM Poly (amidoamine); Pharmaceutical application